Meningkatkan Kemampuan Motorik Halus Anak Melalui Kegiatan Menggunting Polaris di Kelompok A TK Muslimat NU Kedungwuni Kabupaten Pekalongan - Wahida Karmila (AUDIENSI: Jurnal Pendidikan dan Perkembangan Anak, 2022)
The fine motor skills of children in pattern cutting activities in Group A of the Muslimat NU Kedungwuni Kindergarten, Pekalongan Regency for the 2019/2020 academic year, are still very low, only 13% of children are able to cut patterns. This study aims to improve children's fine motor skills through cutting line patterns. The type of research in this research is classroom action research. Research data in the form of data about the ability to cut, data collection instruments with observation sheets, and data collection techniques through observation. Based on the data analysis in the pre-cycle, the learning outcomes of 3 children cut with assistance, 10 children cut according to the pattern, and 2 children cut according to the pattern. In the first cycle, the learning outcomes of 1 child cut with assistance, 8 children cut not according to the pattern, and 6 children cut according to the pattern. In cycle II, 2 children did not cut according to the pattern, and 13 children cut according to the pattern. Based on the results of data analysis and discussion of research results that have been carried out, it can be concluded that through cutting activities according to patterns can improve children's fine motor skills. The results of this study are expected to provide input for teachers in choosing activities. In addition, other researchers can use it as study material to develop further research to improve the quality of the teaching and learning process.